23 Arterial Stiffness and Falls in Older People: Cross-Sectional Data from the Malaysian Elders Longitudinal Research Study (MELoR). (20th December 2019) - Tan, Maw Pin; Mat, Sumaiyah; Kamaruzzaman, Shahrul Bahyah; Mohktar, Mas Sahidayana; Ibrahim, Fatimah
Abstract: Background: Cardiovascular problems such as orthostatic hypotension are common risk factors for falls in older persons. Arterial stiffness has been suggested as the key determinant of cardiovascular risk. Published evidence to support the assumption on the associations between arterial stiffness parameters and falls remains limited. Aim: To determine the association between arterial stiffness and falls in older people. Methods: This was a cross-sectional analysis of MELoR first wave data. Of 446 participants included, 103 reported at least one falls in the past 12 months. The assessment of arterial pulse wave components was performed by non-invasive applanation tonometry of radial artery a SphygmoCor device (AtCor Medical, Sydney, Australia). Result: Participants with mean age 68.28 (7.28) and 60% female were included in this study. Fallers showed significant higher central arterial pressure percentage at heart rate 75bpm compared to the non-fallers [mean (SD): 16.61 (8.16) vs 14.79 (6.89), p=0.026]. The association remained significant after adjustment for age and hypertension. In addition, peripheral diastolic pressure in fallers was significantly lower than non-fallers (p-value=0.049). Conclusion: Augmented index at the heart rate of 75bpm was associated with falls in older people. Thus, this study suggests that this parameter could be the determinants in assessing risk of falls. A prospective study is therefore recommended to determine temporal associations between arterial stiffness and falls.